Kinetic parameters of human aspartate/asparagine-β-hydroxylase suggest that it has a possible function in oxygen sensing - Brewitz, L; Tumber, A; Schofield, CJ (American Society for Biochemistry and Molecular Biology, 2020)
Human aspartate/asparagine-β-hydroxylase (AspH) is a 2-oxoglutarate (2OG) dependent oxygenase that catalyzes the post-translational hydroxylation of Asp- and Asn-residues in epidermal growth factor-like domains (EGFDs). Despite its biomedical significance, studies on AspH have long been limited by a lack of assays for its isolated form. Recent structural work has revealed that AspH accepts substrates with a non-canonical EGFD disulfide connectivity (i.e. the Cys 1–2, 3–4, 5–6 disulfide pattern). Here, we developed stable cyclic thioether analogues of the non-canonical EGFD AspH substrates to avoid disulfide shuffling. We monitored their hydroxylation by solid-phase extraction coupled to MS. The extent of recombinant AspH-catalyzed cyclic peptide hydroxylation appears to reflect levels of EGFD hydroxylation observed in vivo, which vary considerably. We applied the assay to determine the kinetic parameters of human AspH with respect to 2OG, Fe(II), L-ascorbic acid, and substrate and found that these parameters are in the typical ranges for 2OG oxygenases. Of note, a relatively high Km for O2 suggested that O2 availability may regulate AspH activity in a biologically relevant manner. We anticipate that the assay will enable the development of selective small-molecule inhibitors for AspH and other human 2OG oxygenases.